(3GdQSGdI GdeMeOjIs - (3GdOQGRj GdHMQGfj, GHf YUahQ, jhSa Hf CMeO Hf EHQGgje, J(B1186(3g`s ((3MSf Hf LeGd Hf CMeOs)
(3ChdgG (B:s
(3CeG HYO MeO Gdedc GdeGfM(B...(3ajbhd (B...(3jhSa Hf CMeO(B...(3bO SCdfj GdCN GdUGdM(B...(3Cf CcJH dg QSGdI JTJed Ydi LedI ef CMcGe GdehGQjK(B...s
(3BNQgG (B:s
(3gPG BNQ eG LQi Hg Gdbde aj gPg GdQSGdI hSeMJ Hg GdbQjMI GdLGeOI aj gPg GdYLGdI(B...s
(3CJe JCdjag aj BNQ QeVGf (B1155(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B8(3,U(B215s
(3GdPQjYI(B:(3L(B11(3,U(B163(3,Qbe(B1363s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis